Competitive advantage as a mediating effect in the impact of green innovation and firm performance - Novitasari, Maya; Agustia, Dian (Business: Theory and Practice, 2023)
The objective of this study was to measure or assess competitive advantage in mediating the effect of green innovation on firm performance. The data in the study were PROPER companies for the 2010-2018 period and the sample was selected using purposive sampling so that 369 companies were obtained. The results of this study proved that green innovation had a positive effect on competitive advantage, the competitive advantage had a positive effect on firm performance, green innovation had no effect on firm performance, and competitive advantage mediated the effect of green innovation on firm performance. In reducing environmental problems, companies can apply green innovation to increase the company’s competitive advantage and firm performance.